Erratum: evaluation of the performance of manual antimicrobial susceptibility testing methods and disk breakpoints for stenotrophomonas maltophilia (2021)
Volume 65, no. 5, e02631-20, 2021, https://doi-org.ezproxy.unbosque.edu.co/10.1128/AAC.02631-20. We found several typographical errors in our recently published article. The overarching conclusions for the paper remain the same, but some of the data should be changed numerically, as described herein. Table 3 should appear as shown below. The “Gradient strip performance” section in Results should read as follows: The performances of two brands of gradient strips were evaluated against BMD (Table 3). CLSI document M100 breakpoints were used for SXT, MIN, LEV, and CAZ, while EUCAST PK/PD breakpoints were used for CIP and TGC (Table 1). Etest performance met overall acceptance criteria for SXT, MIN, and LEV (Table 3). Overall values for CA with Etest for SXT, MIN, LEV, and CAZ were 99%, 93%, 81%, and 71%, respectively (Table 3). Etest for SXT yielded 1 VME within the acceptable error range for an isolate with an MIC at the breakpoint (4 mg/ml) by BMD. All SXT MEs were resolved with repeat testing. Etest for LEV yielded 1 VME, 18 MIs, and 5 MEs, 3 of which were resolved upon repeat testing. One ME was within 1 doubling dilution of the intermediate MIC breakpoint (Table 3). The majority of MIs (17/18) were within 1 doubling dilution of the intermediate breakpoint, while 1 had an MIC lower than 2 doubling dilutions of the intermediate breakpoint, yielding results that were in the acceptance range (1.7%) (Table 3). The LEV Etest yielded a more resistant result for 17 of the 18 MIs, calling 9 isolates as intermediate when they had a BMD at the susceptible breakpoint (2 mg/ml) (Table S2). Eight of the MIs were called resistant by the LEV Etest when they had a BMD MIC at the intermediate breakpoint (4mg/ml) (Table 3). Initial testing for MIN yielded 1 ME, which was resolved with repeat testing, 0 VME, and 8 MIs. All MI were intermediate by Etest but susceptible by BMD (Table S2). The CAZ Etest strip yielded 9 VMEs, 7 MEs, and 16 MIs, none of which resolved on repeat testing. Of these, 6 VMEs (17%), 1 ME (3%), and 13 MIs (37%) were within 1 doubling dilution of the intermediate breakpoint (Table 3). Six MEs were isolates with an MIC lower than 1 doubling dilution of the intermediate breakpoint (Table 3). The MIC test strip (MTS; Liofilchem, Roseto degli Abruzzi, Italy) performance met the acceptance criteria for SXT, LEV, and MIN (Table 3). Values for CA with MTS for SXT, MIN, LEV, and CAZ were 97%, 99%, 83%, and 72%, respectively. Initial testing with SXT yielded 3 ME, one which resolved with repeat testing, and 1 VME, which was within 1 doubling dilution of the susceptible breakpoint MIC (error rates of 4%) (Table 3). The (Table Presented) MIN MTS yielded 1 MI and no VMEs or MEs. The LEV MTS yielded 0 VME, 18 MIs, and 0 MEs (Table 3). Sixteen of the LEV MIs were within 1 doubling dilution of the intermediate breakpoint MIC. Eight MIs were susceptible by BMD and intermediate by MTS, 2 were resistant by BMD and intermediate by MTS, 5 were intermediate by BMD and resistant by MTS, and 3 were intermediate by BMD and susceptible by MTS (Table S2). Eleven out of 18 MIs had MICs within essential agreement between BMD and MTS. CAZ MTS did not have an acceptable performance (72% CA) and yielded 4 VMEs, 8 MEs, and 19 MIs (Table 3). Six of the MEs were MICs lower than 1 doubling dilution from the intermediate breakpoint (15% error rate), which fell outside the acceptable performance criteria (Table 3). Copyright © 2021 American Society for Microbiology. All Rights Reserved.